Peripheral Developing Odontoma or Peripheral Ameloblastic Fibroodontoma: A Rare Challenging Case - Saede Atarbashi Moghadam; Sepideh Mokhtari (Case Reports in Dentistry)
Peripheral odontogenic lesions are considered to be rare within the classification of odontogenic tumors. They share the same microscopic characteristics of their central counterparts. Here, we report an ulcerated mass of the maxillary gingiva that on histopathological examination was diagnosed as peripheral developing odontoma or peripheral ameloblastic fibroodontoma. The diagnosis of this tumor is challenging and may lead to unnecessary treatment.